Choice‐making, Expectations, and Treatment Positivity: How and When Choosing Shapes Aversive Experiences. (11th February 2013) - Rose, Jason P.; Geers, Andrew L.; Fowler, Stephanie L.; Rasinski, Heather M.
ABSTRACT Every day we use products and treatments with unknown but expected effects, such as using medication to manage pain. In many cases, we have a choice over which products or treatments to use; however, in other cases, people choose for us or choices are unavailable. Does choosing (versus not choosing) have implications for how a product or treatment is experienced? The current experiments examined the role of choice‐making in facilitating so‐called expectation assimilation effects—or situations in which a person's experiences (e.g., discomfort and pain) are evaluated in a manner consistent with their expectations. In Experiment 1, participants were initially exposed to a baseline set of aversive stimuli (i.e., sounds). Next, some participants were given expectations for two "treatments" (i.e., changes in screen display) that could ostensibly reduce discomfort. Critically, participants were either given a choice or not about which of the two treatments they preferred. Participants in a control condition were not provided with treatment expectations. Results revealed that discomfort experiences assimilated to expectations only when participants were provided with choice. Experiment 2 replicated this finding and provided evidence against the idea that demand characteristics and choice‐making unrelated to the core task (i.e., choices without associated expectations) could account for the results. Further, Experiment 2 showed that choosing reduced discomfort because of increased positivity about the treatment. Results are discussed in the context of extant research on choice‐making and expectation effects. Copyright © 2013 John Wiley & Sons, Ltd.